PEMBUATAN ARANG AKTIF DARI LIMBAH AMPAS KELAPA DENGAN KADAR AKTIVATOR HCL BERBEDA (Manufacture of Activated Carbon from Coconut Pulp Waste Using HCl as Activator with Different Concen - Muchlis Raja Uhum; Saipul Bahri Daulay; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2017)
ABSTRACT Activated carbon is a material that has a high carbon content that can be made from organic and inorganic materials, in condition that the materials have a porous structure. The research was aimed to determine the characteristic of moisture content, ash content and pore surface area of activated carbon from coconut pulp waste as well as to improve phsycal quality of the water.The results indicated that the best concentration carbon from coconut pulp waste was by using 15 % HCl activator which produced moisture content of 6,67 %, ash content of  0,52 % and pore surface area of  25,48 mm. The application of the activated carbon by using 15 % HCl activator in water indicated that the water turbidity was 14,33 NTU, colour of the water was very clear and the water had no smell. The result showed that the produced water did reached the water quality standard. Keywords: activated carbon, coconut pulp waste, physical quality of water   ABSTRAK Arang aktif merupakan material yang memiliki kadar karbon tinggi yang dapat dibuat dari bahan organik maupun anorganik, dengan syarat bahan tersebut mempunyai struktur pori. Penelitian ini bertujuan untuk mengetahui karakteristik kadar air, kadar abu, luas permukaan pori arang aktif ampas kelapa serta untuk meningkatkan kualitas fisik air. Hasil penelitian menunjukkan bahwa arang aktif ampas kelapa terbaik dari aktivator HCl 15 % menghasilkan kadar air 6,67 %, kadar abu 0,52 % dan diameter permukaan pori 25,48 mm. Hasil pengaplikasian arang aktif dari aktivator HCl 15 % menghasilkan nilai kekeruhan air 14,33 NTU, warna air sangat jernih dan air tidak berbau. Hasil tersebut sudah memenuhi standar mutu air bersih.   Kata kunci: arang aktif, limbah ampas kelapa, kualitas fisik air